2009
DOI: 10.1152/jn.91337.2008
|View full text |Cite
|
Sign up to set email alerts
|

Substance P Enhances Excitatory Synaptic Transmission on Spinally Projecting Neurons in the Rostral Ventromedial Medulla After Inflammatory Injury

Abstract: Zhang L, Hammond DL. Substance P enhances excitatory synaptic transmission on spinally projecting neurons in the rostral ventromedial medulla after inflammatory injury. J Neurophysiol 102: 1139 -1151, 2009. First published June 3, 2009 doi:10.1152/jn.91337.2008. It has been proposed, but not directly tested, that persistent inflammatory nociception enhances excitatory glutamatergic inputs to neurons in the rostral ventromedial medulla (RVM), altering the activity and function of these neurons. This study used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 78 publications
3
45
1
Order By: Relevance
“…Using this approach, no increase in SubP content was observed on either side of the RVM four hours, four days, or two weeks after CFA treatment. This negative finding was not congruent with the results of earlier pharmacological (Pacharinsak et al, 2008; Hamity et al, 2010; Lagraize et al, 2010), electrophysiological (Budai et al, 2007; Zhang and Hammond, 2009; Brink et al, 2012) and neuroanatomical (Hamity et al, 2014) investigations whose results suggested that CFA treatment may increase SubP release. Measurements in tissue homogenates may not be able to detect small changes in content, changes that are confined to subsets of neurons or changes that occur in specific compartments such as axon terminals.…”
Section: Discussioncontrasting
confidence: 87%
“…Using this approach, no increase in SubP content was observed on either side of the RVM four hours, four days, or two weeks after CFA treatment. This negative finding was not congruent with the results of earlier pharmacological (Pacharinsak et al, 2008; Hamity et al, 2010; Lagraize et al, 2010), electrophysiological (Budai et al, 2007; Zhang and Hammond, 2009; Brink et al, 2012) and neuroanatomical (Hamity et al, 2014) investigations whose results suggested that CFA treatment may increase SubP release. Measurements in tissue homogenates may not be able to detect small changes in content, changes that are confined to subsets of neurons or changes that occur in specific compartments such as axon terminals.…”
Section: Discussioncontrasting
confidence: 87%
“…Thus, ablation of NK-1R expressing neurons in the RVM likely decreased serotonin-dependent descending facilitation. The relationship between NK-1R expressing neurons in the RVM and serotonin is unclear since there is no expression of NK-1Rs in serotonin-containing neurons (Leger et al, 2002; Zhang and Hammond, 2009; Hahm et al, 2011). Therefore, ON cells that possess NK-1Rs may excite serotonin-containing neurons in the RVM indirectly through interneurons that activate descending serotonergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…[84][85][86][87][88][89][90][91][92][93][94][95][96] In summary, all these neurotransmitters released by nociceptive ascending neurons over 'ON'-RVM neurons cause their hyperexcitability (Figure 4). 97 Neuropathic and inflammatory pain also causes changes in PAG neurons. Under these circumstances, the hyperexcitability of nociceptive ascending neurons not only induces sensitization of PAG neurons causing overexpression of several receptors including NMDA/AMPA and SP/NK1 but also overexpression of glutamate and brain-derived neurotrophic factor.…”
Section: Molecular Neuroplasticity Of the Descending Inhibitory Pain mentioning
confidence: 99%